RESISTANCE EVALUATION OF INTRODUCING SPECIES VACCINIUM COVILLEANUM ACCORDING TO THE SECOND AND THE FOURTH COMPONENTS OF WINTER HARDINESS IN BELARUSIAN POLESIE CONDITIONS - S. L. Prikhodko; V. P. Dedkov (Труды по прикладной ботанике, генетике и селекции)
The frost resistance of six varieties of "northern highbush blueberry" (early-ripening - ‘Bluetta’, ‘Spartan’, mid-season - ‘Bluecrop’, ‘Toro’, late-ripening - ‘Elizabeth’, ‘Elliott’) has been studied in the condition of Polesie (southern agro climatic region of the Republic of Belarus) during 2012-2014. It was revealed that late-ripening varieties display lower frost-resistance than early and mid-season varieties on the second and fourth components of winter hardiness.